Ion Channel Gene Mutations Causing Skeletal Muscle Disorders: Pathomechanisms and Opportunities for Therapy - Lorenzo Maggi; Silvia Bonanno; Concetta Altamura; Jean-François Desaphy (Cells, 2021)
Skeletal muscle ion channelopathies (SMICs) are a large heterogeneous group of rare genetic disorders caused by mutations in genes encoding ion channel subunits in the skeletal muscle mainly characterized by myotonia or periodic paralysis, potentially resulting in long-term disabilities. However, with the development of new molecular technologies, new genes and new phenotypes, including progressive myopathies, have been recently discovered, markedly increasing the complexity in the field. In this regard, new advances in SMICs show a less conventional role of ion channels in muscle cell division, proliferation, differentiation, and survival. Hence, SMICs represent an expanding and exciting field. Here, we review current knowledge of SMICs, with a description of their clinical phenotypes, cellular and molecular pathomechanisms, and available treatments.